The Use of Gadgets at Home as a Barrier to Elementary School Students’ Learning: A Literature Review on the Role of Parents and Instructional Intervention Models - Mustakim (Journal of Education, Teaching, and Learning, 2026)
The increasing use of digital gadgets at home has become a significant concern in relation to elementary school students’ learning. While technology offers educational opportunities, excessive and unregulated gadget use may hinder children’s cognitive, social, and academic development. Therefore, this study aimed to examine how gadget use at home becomes a barrier to learning, to analyze the role of parents in mediating children’s digital behavior, and to identify effective instructional intervention models to address these challenges. This study employed a qualitative approach using a Systematic Literature Review (SLR) design. Data were collected from peer-reviewed journal articles and academic books published between 2016 and 2026, retrieved from databases such as Scopus, ERIC, Google Scholar, and ScienceDirect. The selection process followed PRISMA guidelines, and the data were analyzed using thematic analysis. The findings revealed that excessive gadget use disrupts students’ concentration, executive functions, and academic performance, while also negatively affecting social behavior, emotional stability, and physical well-being. Parental mediation, including active guidance, restriction, and co-use strategies, plays a crucial role in minimizing these negative impacts. Additionally, instructional intervention models—such as family-based routines, digital literacy education, and behavioral strategies—were found to be effective in optimizing gadget use for learning purposes. In conclusion, gadget use at home can act as a barrier to learning if not properly managed; however, through effective parental involvement and structured educational interventions, its negative effects can be reduced and its potential benefits maximized.